Sounds of Silence in Times of COVID-19: Distress and Loss of Cardiac Coherence in People With Misophonia Caused by Real, Imagined or Evoked Triggering Sounds - Ferrer-Torres, Antonia; Giménez-Llort, Lydia (Frontiers in Psychiatry, 2021)
The extreme, unprecedented situations in the current COVID-19 pandemic are risk factors for psychosocial stress for the entire population. However, strict confinement had a particular impact on people suffering from misophonia and their families. Misophonia is a condition in which hearing certain sounds triggers intense anger, disgust and even severe autonomic nervous system responses. This prospective cohort study examined the impact of strict confinement (Spain, March 14–June 21, 2020) on a sample of 24 people (16 women and eight men) who had been diagnosed with moderate to extreme misophonia and were regularly attending a medical psychology center in Barcelona. The 3-month period of confinement caused general emotional maladjustment, distress, and a transitory crisis. Long-term biomonitoring of their heart variability rate (HRV) enabled to identify a significant increase in physiological arousal after the confinement period, which had already been recorded in a loss of cardiac coherence under basal rest/relaxation conditions. Certain auditory stimuli triggered adverse responses, lowered HRV scores, and an increased stress level and heart rate. Loss of cardiac coherence in their responses to these auditory stimuli (triggering mouth, nose and other sounds), as well as to non-triggering mouth, nose and other sounds was increased when compared to two assessments performed during the previous year. Despite the limited sample size, sex differences were observed in the incidence. Loss of cardiac coherence worsened with the severity of the misophonia. Most importantly, imagined or evoked triggering sounds, as well as real ones, were enough to cause the aversive responses, as displayed by the increased loss of cardiac coherence with respect to the at-rest basal level. A semi-structured interview revealed the exceptional nature of the situations, increased hyper-sensorial sensitivity, fear of being infected with or dying from COVID-19, the patients' coping strategies, and the difficulties and constraints they faced. Finally, the article gives recommendations for better management of misophonia. Improved knowledge of this disorder would help address the current lack of health and social care, hopefully preventing this shortfall's impact on social and affective relationships, which are particulary important for well-being now and in the coming periods of physical distancing measures.